Extending UML templates towards flexibility - Farinha, J. (Proceedings of the 2nd Workshop on Flexible Model Driven Engineering co-located with ACM/IEEE 19th International Conference on Model Driven Engineering Languages & Systems (MoDELS 2016), 2016)
UML templates are generic model elements that may be instantiated as domain specific solutions by means of parameterization. Some of the elements in a template definition are marked as parameters, implying that these must be sub-stituted by elements of the domain model, so to get a fully functional instance of the template. On parameter substitutions, UML enforces that the parame-tered element and its substitute must be of the same kind (both classes, both at-tributes, etc.). This paper shows that this constraint confines the applicability of templates and proposes an alternative that, by allowing substitutions among elements of different kinds, broadens that applicability. Cross-kind substitu-tions, however, require adequate semantics for the Binding relationship. Such semantics are proposed as model transformations that must complement the plain substitutions preconized by UML. Examples of such transformations are provided for activities in a template being expanded into a bound element.